PENERAPAN MODEL ROLE PLAYING DALAM PEMBELAJARAN IPS KELAS IV SD NEGERI TABA TINGGI - Triana Anjarsari; Aren Frima; Andri Valen (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the completeness of the fourth grade social studies learning at SD Negeri Taba Tinggi after implementing the role playing model. The research method used was pre experimental design. Data collection techniques in research using essay tests. The data analysis techniques for the Post test showns that the zvalue is 3,04. This result is compared with the ztabel value at a significant completed of 5% namely 1,64. Based on these result it is known that the zvalue (3,04) > ztabel (1,64). So it can be concluded that the application of the Role Playing model in social studies learning at SD Negeri Taba Tinggi after the Role Playing model is Significant applied. Keywords: Application, Role Playing, Social Studies Learning.